ADCY3: the pivotal gene in classical ketogenic diet for the treatment of epilepsy - Lin, Mingxing; Gong, Jiayin; Wu, Luyan; Lin, Xin; Zhang, Yuying; Lin, Wanhui; Huang, Huapin; Zhu, Chaofeng (Frontiers in Cellular Neuroscience, 2024)
Epilepsy is a common neurological disorder characterized by recurrent epilepsy episodes. As a non-pharmacological treatment, the ketogenic diet has been widely applied in treating epilepsy.However, the exact therapeutic mechanism of the ketogenic diet for epilepsy remains unclear. This study investigates the molecular mechanisms of the ketogenic diet in regulating fatty acid metabolism and activating the ADCY3-initiated cAMP signaling pathway to enhance neuronal inhibition and thereby treat epilepsy. Meta-analysis reveals that the ketogenic diet is superior to the conventional diet in treating epilepsy. Animal experiments demonstrate that the ketogenic diet is more effective than the conventional diet in treating epilepsy, with the best results achieved using the classic ketogenic diet. Transcriptome sequencing analysis identifies six essential genes, among which ADCY3 shows increased expression in the ketogenic diet. In vivo experiments confirm that the activation of the cAMP-PKA signaling pathway by ADCY3 enhances neuronal inhibition and improves epilepsy control. Clinical observations indicate that the ketogenic diet improves patient epilepsy episodes by regulating the ADCY3-initiated cAMP signaling pathway.